Pharmacological rescue of specific long QT variants of KCNQ1/KCNE1 channels - Zou, Xinle; Wu, Xiaoan; Sampson, Kevin J.; Colecraft, Henry M.; Larsson, H. Peter; Kass, Robert S. (Frontiers in Physiology, 2022)
The congenital Long QT Syndrome (LQTS) is an inherited disorder in which cardiac ventricular repolarization is delayed and predisposes patients to cardiac arrhythmia and sudden cardiac death. LQT1 and LQT5 are LQTS variants caused by mutations in KCNQ1 or KCNE1 genes, respectively. KCNQ1 and KCNE1 co-assemble to form critical IKS potassium channels. Beta-blockers are the standard of care for the treatment of LQT1, however, doing so based on mechanisms other than correcting the loss-of-function of K+ channels. ML277 and R-L3 are compounds that enhance IKS channels and slow channel deactivation in a manner that is dependent on the stoichiometry of KCNE1 subunits in the assembled channels. In this paper, we use expression of IKS channels in Chinese Hampster Ovary (CHO) cells to study the potential of these two drugs (ML277 and R-L3) for the rescue of LQT1 and LQT5 mutant channels. We focused on the LQT1 mutation KCNQ1-S546L, and two LQT5 mutations, KCNE1-L51H and KCNE1-G52R. We found ML277 and R-L3 potentiated homozygote LQTS mutations in the IKs complexes-KCNE1-G52R and KCNE1-L51H and in heterogeneous IKs channel complexes which mimic heterogeneous expression of mutations in patients. ML277 and R-L3 increased the mutant IKS current amplitude and slowed current deactivation, but not in wild type (WT) IKS. We obtained similar results in the LQT1 mutant (KCNQ1 S546L/KCNE1) with ML277 and R-L3. ML277 and R-L3 had a similar effect on the LQT1 and LQT5 mutants, however, ML277 was more effective than R-L3 in this modulation. By directly studying the treatment of LQT1 and LQT5 mutations with ML277 and R-L3, we will understand the potential utility of these activators as options in LQTS precision medicine.